2014
DOI: 10.1155/2014/597103
|View full text |Cite
|
Sign up to set email alerts
|

Variability in the Branching Pattern of the Internal Iliac Artery in Indian Population and Its Clinical Importance

Abstract: Internal iliac artery (IIA) is one of the terminal branches of the common iliac artery and is the prime artery of pelvis. The artery has many parietal and visceral branches and hence the variations are frequently noted. The larger branches, namely, the inferior gluteal artery, the superior gluteal artery, and the internal pudendal artery, show sufficient regularity in their patterns of origin to allow typing. The variability of the IIA and its branching pattern were studied by dissecting sixty-eight male pelvi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
22
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(29 citation statements)
references
References 7 publications
1
22
0
Order By: Relevance
“…This study was the first to elucidate these patterns, and our findings have important implications for surgeons. Since Adachi first classified the IIA branching variations into five types [3], several studies have investigated the distributions of branching patterns in different populations [4][5][6]. Although those studies analyzed arterial variations in detail, they only assessed the IIA, independent of other vessels.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study was the first to elucidate these patterns, and our findings have important implications for surgeons. Since Adachi first classified the IIA branching variations into five types [3], several studies have investigated the distributions of branching patterns in different populations [4][5][6]. Although those studies analyzed arterial variations in detail, they only assessed the IIA, independent of other vessels.…”
Section: Discussionmentioning
confidence: 99%
“…Only a few studies have demonstrated the morphological variability in the courses of the internal iliac artery, vein, or obturator vessels. Moreover, most of those studies were based on a small series or they addressed the variability of an individual artery or vein [3][4][5][6][7][8][9]. During surgery, it is also quite important to understand the inter-relationships between intrapelvic organs, in addition to individual variability, and these issues are rarely studied.…”
Section: Introductionmentioning
confidence: 99%
“…I recently came across an interesting and useful article on “Variability in the Branching Pattern of the Internal Iliac Artery in Indian Population and Its Clinical Importance,” by Sakthivelavan et al [1]. As a practicing obstetrician who has served in several parts of developing countries, I would first like to thank the authors for their commendable desire to contribute to a topic of great clinical significance.…”
mentioning
confidence: 99%
“…Conventionally, the IIA is ligated 5 cm distal to the bifurcation of the common iliac artery as it is said to spare the posterior division and avoid gluteal ischemia and necrosis. However, I was quite surprised to see that in as high as 25.9% of the cases this might not be the case due to anatomical variation [1]. It was also interesting to note the anomalous origin of the obturator artery from the posterior division in 6.8% of cases [1], as the parietal branches of the obturator play an important role in collateral circulation.…”
mentioning
confidence: 99%
See 1 more Smart Citation